Development of the asymptotic state concept for soils and its application to slope stability analysis - Chu, Jian. (2008)
A new state concept, the so-called asymptotic state, had been proposed based on experimental studies on sand and clay. Further experimental study was carried out on a laboratory compacted residual soil to verify whether the asymptotic state could also be established for residual soils. Compaction, consolidation, triaxial drained, triaxial undrained, stress/strain path, and ring shear tests were conducted to establish the stress-strain behaviour of the tested soil.